Childhood cancer survivor cohorts in Europe. (May 2015) - Winther, Jeanette F.; Kenborg, Line; Byrne, Julianne; Hjorth, Lars; Kaatsch, Peter; Kremer, Leontien C. M.; Kuehni, Claudia E.; Auquier, Pascal; Michel, Gérard; de Vathaire, Florent; Haupt, Riccardo; Skinner, Roderick; et al.
Abstract With the advent of multimodality therapy, the overall five-year survival rate from childhood cancer has improved considerably now exceeding 80% in developed European countries. This growing cohort of survivors, with many years of life ahead of them, has raised the necessity for knowledge concerning the risks of adverse long-term sequelae of the life-saving treatments in order to provide optimal screening and care and to identify and provide adequate interventions. Childhood cancer survivor cohorts in Europe. Considerable advantages exist to study late effects in individuals treated for childhood cancer in a European context, including the complementary advantages of large population-based cancer registries and the unrivalled opportunities to study lifetime risks, together with rich and detailed hospital-based cohorts which fill many of the gaps left by the large-scale population-based studies, such as sparse treatment information. Several large national cohorts have been established within Europe to study late effects in individuals treated for childhood cancer including the Nordic Adult Life after Childhood Cancer in Scandinavia study (ALiCCS), the British Childhood Cancer Survivor Study (BCCSS), the Dutch Childhood Oncology Group (DCOG) LATER study, and the Swiss Childhood Cancer Survivor Study (SCCSS). Furthermore, there are other large cohorts, which may eventually become national in scope including the French Childhood Cancer Survivor Study (FCCSS), the French Childhood Cancer Survivor Study for Leukaemia (LEA), and the Italian Study on off-therapy Childhood Cancer Survivors (OTR). In recent years significant steps have been taken to extend these national studies into a larger pan-European context through the establishment of two large consortia – PanCareSurFup and PanCareLIFE. The purpose of this paper is to present an overview of the current large, national and pan-European studies of late effects after childhood cancer. This overview will highlight the strong cooperation across Europe, in particular the EU-funded collaborative research projects PanCareSurFup and PanCareLIFE. Overall goal. The overall goal of these large cohort studies is to provide every European childhood cancer survivor with better care and better long-term health so that they reach their full potential, and to the degree possible, enjoy the same quality of life and opportunities as their peers.